Pengaruh Manajemen Waktu dan Pendampingan Akademik Terhadap Prestasi Akademik - Salwa Agustin; Chotimatus Syifa; Suparmi Suparmi (Jurnal Konseling dan Psikologi Indonesia, 2026)
Academic achievement is one of the main indicators of the success of the educational process and is influenced by students' ability to manage their learning process. This study aims to analyze the effect of study time management and academic mentoring on student academic achievement. The study used a quantitative approach with a descriptive-associative design. A total of 100 students in Surakarta were selected as respondents through a total sampling technique and completed a questionnaire compiled based on theoretical indicators of each variable. All research instruments have undergone validity and reliability tests, which were declared suitable for use because they have high internal consistency. Data analysis was conducted using multiple linear regression through the SPSS program. The results showed that partially study time management has a positive and significant effect on student academic achievement, while academic mentoring did not have a significant effect. Nevertheless, both variables simultaneously had a significant influence, contributing 69.6% to academic achievement. This finding indicates that students' ability to plan, organize, and control study time is a dominant factor in determining academic success. On the other hand, academic mentoring still requires quality improvement to contribute more effectively to student learning outcomes. This study implies that strategies to strengthen time management and optimize academic mentoring are important for improving overall academic achievement.